2007
DOI: 10.1002/asia.200700015
|View full text |Cite
|
Sign up to set email alerts
|

Triazole: the Keystone in Glycosylated Molecular Architectures Constructed by a Click Reaction

Abstract: The copper(I)-catalyzed modern version of the Huisgen-type azide-alkyne cycloaddition to give a 1,4-disubstituted 1,2,3-triazole unit is introduced as a powerful ligation method for glycoconjugation. Owing to its high chemoselectivity and tolerance of a variety of reaction conditions, this highly atom-economic and efficient coupling reaction is especially useful for the effective construction of complex glycosylated structures such as clusters, dendrimers, polymers, peptides, and macrocycles. In all cases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(91 citation statements)
references
References 106 publications
0
88
0
3
Order By: Relevance
“…Reduction in the d-spacing after functionalization, indicated that upon functionalization, the structure of the samples was changed due to the amorphization of the material by introducing the organic moiety into the interlayer spacing of GO. For all four different rGOf, one crucial peak can be seen at 2358 cm −1 indicating the stretching of C-N, proving the success of azide-alkyne coupling reaction on the GO sheets [27,31]. The intensities of the peaks indicating the presence of oxygen-containing functionalities showed a dramatic reduction from GO to rGOf.…”
Section: Materials Characterizationmentioning
confidence: 81%
“…Reduction in the d-spacing after functionalization, indicated that upon functionalization, the structure of the samples was changed due to the amorphization of the material by introducing the organic moiety into the interlayer spacing of GO. For all four different rGOf, one crucial peak can be seen at 2358 cm −1 indicating the stretching of C-N, proving the success of azide-alkyne coupling reaction on the GO sheets [27,31]. The intensities of the peaks indicating the presence of oxygen-containing functionalities showed a dramatic reduction from GO to rGOf.…”
Section: Materials Characterizationmentioning
confidence: 81%
“…In both cases, multiple azide-alkyne coupling allowed the sugar fragments to be linked to the calix [4]arene scaffold through 1,4-disubstituted 1,2,3-triazole tethers, thus leading to the metaphoric view of the triazole as a formidable keystone in glycosylated molecular architectures. [23] With the above azido-activated silica supports in hand, ethynyl C-galactoside 1 and propargyl O- Table 1. Surface coverage data of the azido-activated silica gels obtained in a single step and the prepared sugar-silica gels.…”
Section: Immobilization Of Carbohydratesmentioning
confidence: 99%
“…Synthesis as well as application of 1,2,3-triazole containing simple glycosides, oligosaccharides, glycomacrocycles, glycoclusters, glycodendrimers, glycopeptides, glycoarrays, glycopolimers and glycosylated biomolecules were surveyed in several reviews. [3][4][5][6] 1-Glycosyl-1,2,3-triazole derivatives were obtained from relatively easily available glycosyl azides by using diverse Cu(I) sources.…”
Section: Introductionmentioning
confidence: 99%
“…In situ reduction of Cu(II) salts, usually CuSO 4 or Cu(OAc) 2 by Naascorbate or L-ascorbic acid [7][8][9][10][11][12][13][14][15][16] as well as by Cu turnings 11,17 is one of the most commonly used possibilities for the catalysis, whereby, with unprotected glycosyl azides, addition of o-phenylenediamine 18 proved advantageous. CuI is another often applied catalyst in the presence of either DIPEA or Et 3 N with TBTA (N,N,Ntris-[(1-benzyl-1H-1,2,3-triazole-4-yl)methy]amine).…”
mentioning
confidence: 99%